Fragment shape and size, landscape permeability and fragmentation level as predictors of primate occupancy in a region of Brazilian Cerrado - Thallita Oliveira Grande; Raony Macedo Alencar; Paulo Pinheiro Ribeiro; Fabiano Rodrigues Melo (Acta Scientiarum. Biological Sciences, 2020)
Human activities result in the formation of a mosaic of forest patches within a non-habitat matrix. The response of the local biodiversity to changes in land-use may occur at different scales. It is important to evaluate the effects of the attributes of both the patches and the surrounding landscape on the occupancy of forest patches by animal populations. Here, we assessed the predictive potential of local (basal area, tree density), patch (size, shape) and landscape scale (total area of forest, number of patches, matrix permeability, patch proximity) variables on the occupancy of forest patches by the syntopic primates Alouatta caraya, Sapajus libidinosus and Callithrix penicillata in the city of Goiânia in the Cerrado region of central Brazil. We used playback to survey primate populations in 22 focal patches and assessed the landscape within a 1000 m buffer zone around each site. In A. caraya, occupancy was influenced by the shape of the focal patches, the amount of forest and fragmentation level of the landscape. Focal patch size and the permeability of the matrix were the principal determinants of the occupancy of S. libidinosus. None of the predictors influenced patch occupancy in C. penicillata, and the structure of the vegetation did not influence occupancy in any of the species. The preservation of as many forest patches as possible, both large and small, as well as gallery forests, and the enhancement of matrix permeability will be essential for the long-term conservation of the syntopic primates of the Cerrado of central Brazil.